1989
DOI: 10.1002/ar.1092250411
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic development of the posterolateral structures of the knee

Abstract: The development of the structures in the posterolateral corner of the knee was studied in fifteen human embryos and seventeen fetuses by means of serial sections in the coronal and sagittal planes. The attachments of the lateral meniscus and fibular head to the popliteal tendon and muscle are formed during the process of cavitation that forms the bursa. The connection between the tendon and the posterior border of the lateral meniscus forms obliquely to follow the direction of the muscle and tendon. The edge o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 6 publications
0
15
0
1
Order By: Relevance
“…The current authors thought this unit from the popliteus insertion on the femur to the popliteal fibula insertion on the fibular acts as a ligament that indirectly connects the tibia to the lateral femur when the knee flexes and the lateral ligament relaxes. 27 Watanabe et al 39 showed that the anterior portion of the popliteus tendon tightens in flexion and is capable of resisting rotation. In the current study, sectioning the femoral insertion of the popliteus had a similar effect on external rotation as that of sectioning the popliteal muscle belly and the popliteofibular ligament reported by Shahane et al 31 In that study sectioning of the popliteus muscle only did not result in significantly increased external rotation, most likely because the popliteofibular and popliteofemoral insertions were intact.…”
Section: Discussionmentioning
confidence: 98%
“…The current authors thought this unit from the popliteus insertion on the femur to the popliteal fibula insertion on the fibular acts as a ligament that indirectly connects the tibia to the lateral femur when the knee flexes and the lateral ligament relaxes. 27 Watanabe et al 39 showed that the anterior portion of the popliteus tendon tightens in flexion and is capable of resisting rotation. In the current study, sectioning the femoral insertion of the popliteus had a similar effect on external rotation as that of sectioning the popliteal muscle belly and the popliteofibular ligament reported by Shahane et al 31 In that study sectioning of the popliteus muscle only did not result in significantly increased external rotation, most likely because the popliteofibular and popliteofemoral insertions were intact.…”
Section: Discussionmentioning
confidence: 98%
“…In the 12 week old knee the CS sulphation motifs had a widespread distribution throughout the rudiments however by 14 weeks gestational age the CS sulphation motifs had a more defined distribution pattern in areas of tissue transition. Several studies have extensively examined the development of the human foetal knee joint [2,3,[6][7][8]24,[32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Pur essendo stati descritti per la prima volta da Poirer e Charpy nel 1892, sono stati tuttavia poco studiati nonostante la loro importanza funzionale e clinica. Alcuni Autori hanno identificato in feti di 10 settimane le prime vestigia del legamento meniscofemorale di Wrisberg; al contrario altri Autori non hanno trovato evidenze di questo legamento fino alla 12,5 settimana di sviluppo [23][24][25].…”
Section: Discussioneunclassified